How should severity be understood in the context of reproductive genetic carrier screening?. (6th February 2023) - Dive, Lisa; Archibald, Alison D.; Freeman, Lucinda; Newson, Ainsley J.
Abstract: Reproductive genetic carrier screening provides information about people's chance of having children with certain genetic conditions. Severity of genetic conditions is an important criterion for their inclusion in carrier screening programmes. However, the concept of severity is conceptually complex and underspecified. We analyse why severity is an important concept in carrier screening and for reproductive decision‐making and show that assessments of severity can also have normative societal implications. While some genetic conditions are unambiguously associated with a high degree of suffering, there are many factors that contribute to how severe a condition is perceived to be, and perspectives will vary. Attempts to classify genetic conditions according to their severity tend to prioritise biomedical information at the expense of incorporating qualitative aspects of the impact of genetic conditions on people's lives. Further complexity arises because some genotypes can present with variable phenotypes and because some conditions are not always experienced in the same way by all people who have them. To acknowledge this complexity, we argue that an understanding of severity needs to distinguish between the severity of a genetic condition—requiring a generalised approach for purposes of policy development and programme design—and the severity of an instance of a genetic condition in a particular person. Families making reproductive decisions also require access to diverse experiences of the qualitative aspects of living with genetic conditions. As a result, reproductive carrier screening programmes must recognise and respond to the complexity inherent in determining the severity of genetic conditions.